GAGASAN ISLAMISASI ILMU PENGETAHUAN SEBAGAI PONDASI PENDIDIKAN ISLAM MENURUT SYED MUHAMMAD NAQUIB AL-ATTAS - Basith, Yudril (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2024)
Abstract: This study aims to examine Syed Muhammad Naquib Al-Attas's idea of ​​the Islamization of science as a basis for the reconstruction of the Islamic education system. This study was motivated by concerns about the influence of secularism and westernization that caused the de-Islamization of Muslim thought. To overcome this problem, Al-Attas proposed the concept of the Islamization of science which aims to free science from non-Islamic values ​​and harmonize it with Islamic principles based on the Qur'an and Sunnah. This article uses a qualitative research method with a library research type. The main data source is the written works of Syed Muhammad Naquib Al-Attas, such as books, journals, and other writings. Secondary data was obtained through other literature relevant to the topic of the Islamization of science and the concept of Islamic education to enrich the discussion. The results of the study show that Al-Attas's Islamization of science is built on an Islamic worldview that is sourced from the teachings of monotheism. The epistemology of science needs to be reconstructed in line with Islamic principles by placing spiritual aspects as its foundation. Al-Attas also proposed the concept of ta'dib as a model of Islamic education that integrates physical, intellectual, and spiritual aspects with adab as the core of its method.